The Mathematical Reasoning of the Quran Reciting Student by the Quran Recitation Ability - Azkiya Salsabila; Farida Nurhasanah; Arum Nur Wulandari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2022)
Reciting the Quran is a good habit that can improve people's cognitive abilities, including reasoning. However, according to Bloom's theory, memorization is categorized as the lowest cognitive domain, while according to NCTM, the reasoning is included in the higher-order thinking process. Hence, there is a contradiction in theories of thinking. This study aims to describe the type of reasoning of reciting the Quran students based on their recitation of the Quran ability. This research method is qualitative with a case study approach. The instrument used in this study was a reasoning test and interview guidelines. The results showed that 3 of 4 subjects with high recitation ability used creative reasoning, only one with medium recitation ability used algorithmic reasoning, and none with low recitation ability used a specific reasoning type.